MAPPING LEADING LOCAL CULTURE OF CIREBON TOURISM SECTOR USING GEOGRAPHIC INFORMATION SYSTEM (GIS) - Chairun Nas; Wanda Ilham (Universitas Islam Kuantan Singingi, 2021)
The tourism sector is able to increase regional income, one of them is local cultural tourism. Cirebon as a cultural heritage city, it makes cultural tourism as leading regional tourism. Cirebon government always promote the leading cultural tourism of Cirebon city to tourists. However, the limited presentation of information to tourists has made some sectors of local cultural tourism untouched by tourists. The purpose of this research is to map the leading cultural tourism objects to be implemented into a system that can provide information of location and description for cultural tourism objects. In this research, the data was used the map of Cirebon city and 15 types of research object data in the tourism sector. They were processed and implemented into a Geographical Information System (GIS) and will be able to become a medium for Cirebon government to promote its leading cultural tourism.